2006
DOI: 10.1088/0953-8984/19/1/016203
|View full text |Cite
|
Sign up to set email alerts
|

Breath figure pattern formation as a means to fabricate micro-structured organic light-emitting diodes

Abstract: We demonstrate a procedure for fabricating micro-structured organic light-emitting diodes (micro-LEDs) based on so-called breath figure (BF) pattern formation. In the latter process water vapour is condensed on the surface of a spread polymer solution to form droplets that close pack into ordered arrays and that transfer the BF pattern into the resulting solid thin polymer film. Here, we generate a silicone elastomer negative replica of the BF pattern and use it as a master for solvent-assisted micro-moulding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 35 publications
0
15
0
1
Order By: Relevance
“…They added an insulating layer of polyimide between the active layer and the metal layer. 491 By patterning the PI layer with a PDMS stamp, a dot-array OLED was also obtained, which had current and power efficiencies twice as high as those for nonpatterned OLEDs.…”
Section: Optical and Optoelectronic Devicesmentioning
confidence: 99%
“…They added an insulating layer of polyimide between the active layer and the metal layer. 491 By patterning the PI layer with a PDMS stamp, a dot-array OLED was also obtained, which had current and power efficiencies twice as high as those for nonpatterned OLEDs.…”
Section: Optical and Optoelectronic Devicesmentioning
confidence: 99%
“…Bradley et al. tried a different way of producing a patterned hole transport layer (HTL) using a MLA‐like PDMS stamp 65. The continuous active layer and other layers were then deposited onto the patterned HTL.…”
Section: Bfa Applicationsmentioning
confidence: 99%
“…Due to the current and power efficiency being higher than those of non-patterned devices, the procedure introduced in this paper has significant potential for organic device fabrication without the requirement of a complicated subtractive patterning process. 217 Zhao et al reported the synthesis of honeycomb ordered polycarbonate films in chloroform, dichloromethane, and tetrahydrofuran. Pore sizes increased with RH and decreased with an increase in polymer concentration.…”
mentioning
confidence: 99%